Scrapbook Media On Increasing The Knowledge Of Mother Todders In Stunting Prevention In Lipah Rayeuk Village Jeumpa District, Bireuen Regency - Desita, Desita; Sari, Fatimah; Kasjono, Heru Subaris (International Journal of Health Sciences, 2024)
The incidence of short toddlers or often called stunting is one of the main nutritional problems faced by toddlers in Indonesia today. The results of the 2022 Indonesian Nutrition Status Survey (SSGI) for each province throughout Indonesia, Aceh is in the fourth highest position for stunting cases with a percentage (31.2%). The first position is the province, namely West Sulawesi (35.0 %), second is Papua (34.6%), third is West Nusa Tenggara (32.7%). The lowest position is the province of Bali (8.0 % ) and followed by the second lowest, namely DKI Jakarta (14.8%). This research method is quantitative using a Quasy Experimental design method with a Two-Group Pretest-Posttest Design. The sampling technique was the total population as 41 people in the intervention group and 41 people in the control group. The research results showed that the average value of knowledge about stunting in the intervention group was 28.1465 and the control group was 21.5854. Thus, from descriptive statistics it can be concluded that there is a difference in the average knowledge of mothers of toddlers about stunting between the intervention group and the control group. Sig value. Levene's Test For Equality of Variances is 0.557 > 0.05, so it is guided by the value contained in the "Aqual variances assumed" table, namely the Sig value. (2-tailed) of 0.000 < 0.05, meaning that there is an influence of the use of scrapbook media in health promotion on increasing the knowledge of mothers under five in preventing stunting in Lipah Rayeuk Village, Jeumpa District, Bireuen Regency in 2024. The conclusion is that there is an influence of the use of scrapbook media in health promotion on Increasing the knowledge of mothers of toddlers in preventing stunting in Lipah Rayeuk Village, Jeumpa District, Bireuen Regency was declared effective.